“It's a good distraction from the mayhem of reality”: a reflexive thematic analysis on the role of video games to support coping during a crisis - Farmer, George; Higson-Sweeney, Nina; Fullwood, Chris (Frontiers in Digital Health, 2025)
IntroductionVideo games have been shown to offer psychological benefits to gamers during times of stress. One recent, salient example of a stress-inducing event was the COVID-19 pandemic, which created periods of social isolation and uncertainty on a global scale. The current study offers a glimpse into the lives of video gamers during the COVID-19 pandemic and the role of video games in navigating day-to-day stresses during a crisis.MethodsParticipants (n = 13) were recruited online via volunteer sampling and conducted text-based structured interviews via Skype or via email. Using an interview guide developed for this study, participants were asked questions regarding demographic traits such as age, gender, and employment status, as well as questions regarding their current video game play at the time of the interview and general questions, such as whether video games offered any perceived benefits during the COVID-19 lockdown.ResultsReflexive thematic analysis of 13 interviews generated three themes that focus on video games, coping, and well-being. For many participants, video games provided what the lockdown took away: permitting the restoration of agency, community, and a sense of purpose. Immersing oneself in video games was a proactive coping mechanism for some but protective for others, suggesting a range of strategies that likely differed in effectiveness. Finally, gamers discussed the tension between viewing gaming as a beneficial and valuable activity versus unproductive time-wasting.DiscussionQualitative results are evaluated through the lens of self-determination theory. The use of video games to deal with the day-to-day stresses of the COVID-19 pandemic illustrates teachable moments that speak to video gaming as a compensatory activity during times of crisis, which applies to future global health events beyond COVID-19.